Aspek Moral Dalam Novel Ayah Menyayangi Tanpa Akhir Karya Kirana Kejora: Kajian Sosiologi Sastra Dan Implementasinya Sebagai Pembelajarandi SMA - Hidayat, Faisal; , Dr. Nafron Hasyim (2016)
The research towards a novel entitled Ayah MenyayangiTanpaAkhirby KiranaKejora had three aims. (1) Describing the structure that builds the novel. (2) Describing morality aspect within the novel. (3) Describing the results into Senior High School literary study. This research included the qualitative descriptive research by using the embedded case study research. The source data of this research is a novel entitled Ayah MenyayangiTanpaAkhirwritten by KiranaKejora. The primary data in this research taken from the same title which is explained over morality values and the structural of literature. Yet, the secondary data are the articles and the internet sources realted to this aims of research. The data collecting technique used in this research is the technique of library sciences, watches on, and noting. As for data validation technique that use in this research is triangulation data.The data analysis technique used in this research is the dialectics. The structural analysis glimpsed that the novel shown a sincere loves and responsibilities from a father. The main character is ArjunaDewangga. Settled in a form forward-back plotline story. This novel provides settings of time, setting of time and social angles. As used to be seen in the same tie of this fiction, it is all about good and bad sides to be at. The aspects of favor moralities including responsibility, honesty, low profile, braveness, realistic and critical aspect as well. The aspect bad moralities including irresponsibility, dishonesty, arrogances, poor mentality, illogical and diacritical as well. The results would be implemented into the literary study of Senior High School through Kurikulum Tingkat SatuanPendidikan (KTSP)StandarKompetensi (SK) 7 that taught of tales Indonesian literary works as well as the translated works. Keywords: moral aspects, literary sociology, and literary study.